ПРОБЛЕМИ ІНТЕГРАЦІЇ ВІДНОВЛЮВАНИХ ДЖЕРЕЛ ЕЛЕКТРОЕНЕРГІЇ В «СЛАБКІ» ЕЛЕКТРИЧНІ МЕРЕЖІ - Кириленко , О.В.; Павловський , В.В.; Лук’яненко , Л.М.; Трач , І.В. (Інститут електродинаміки НАН України, Київ, 2012)
The features of the connection ofpower plants constructed using renewable sources of energy to electrical networks and their impact on the opei-ating conditions of such networks are considered. The key point that should be considered when selecting the location of such stations are identified. References 3.